Prevalence of Commonly Abused Drugs Detected from Drug Testing in Unnatural Death Cases During 1-Year Period at Thammasat University Hospital - Tangsermkijsakul, Aphinan; Pipatchotitham, Tossanai (Asian Medical Journal and Alternative Medicine, 2022)
Objective: To determine the prevalence of commonly abused drugs (CAD) detected in unnatural death cases at Thammasat University Hospital (TUH) in 1 year and also evaluate drug prevalence data to propose appropriate toxicology panels used for autopsied deaths at TUH. Methods: A descriptive cross-sectional study was conducted and unnatural death cases in 5 police stations sent to TUH for a medico-legal investigation from March 2020 to February 2021 were recruited in this study. All police records and autopsy reports were documented for demographic data. In this study, drug preliminary tests were performed with rapid chromatographic immunoassay test kits for 5 common drug classes including amphetamines, benzodiazepines (BZD), cannabinoids, opioids, and ketamine. Blood samples from cases with preliminary positive results were analyzed with the confirmatory tests. Results: Two hundreds and sixty five autopsy cases were recruited in this study. Forty cases were positive for at least 1 substance and the prevalence of CAD detected at TUH in 1 year was 15.09%. The prevalence of all 5 drug classes among 4 police stations ranged from 13.56 to 16.26%. However, there was no positive cases for CAD in the highway station area. The highest prevalence by drug was amphetamine-type stimulants (ATS) (8.68%), followed by BZD (4.91%), delta 9-tetrahydrocannabinol (1.13%), morphine (0.75%), and ketamine (0.38%), respectively. The highest prevalence classified by manner of death that CAD were detected was suicide (25%), followed by accident (16.67%). Conclusions: Five common drug classes could be detected in autopsy cases at TUH for 15.09%. ATS and BZD were presented with high prevalence throughout almost all areas of our responsibility and they should be in the routine toxicologic testing.